2018
DOI: 10.3389/fphar.2018.00425
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality and Potential Efficacy of Commercial Extracts of Rhodiola rosea L. by Analyzing the Salidroside and Rosavin Content and the Electrophysiological Activity in Hippocampal Long-Term Potentiation, a Synaptic Model of Memory

Abstract: Rhodiola rosea L. roots and rhizome extracts are active ingredients in adaptogenic herbal medicinal products (HMP) and dietary supplements for temporary relief of symptoms of stress, such as fatigue and weakness. R. rosea extract has a stimulating effect on the CNS, suggesting potential benefits on cognitive functions, memory, learning, and attention. The reproducible efficacy and quality of preparations of the underground parts of R. rosea depend on the highly variable content of the active markers, salidrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
1
20
0
2
Order By: Relevance
“…The principal raw material used for the production of R. rosea supplements are the rhizomes, and some of the most popular preparations, such as Arctic RootÂŽ (based on the standardised SHR‐5 extract), 11 VitanoÂŽ (WSÂŽ 1375 extract), 12 ADAPT‐232 forteÂŽ (fixed combination of R. rosea , Eleutherococcus senticocus and Schisandra chinensis extracts), 13 are registered as herbal medicines in Europe 14 . The SHR‐5 is defined as R. rosea root and rhizome extract with a herb‐extract ratio 2.5–5:1 (extraction solvent 70% ( v / v ) ethanol), 15 containing 0.15% p ‐tyrosol, 2.14% salidroside and 4.77% rosavins 16 . The WSÂŽ 1375 has an herb‐extract ratio 1.5–5:1 (solvent 67–70% ( v/v ) ethanol) and contains 1% salidroside and 2.71% rosavin, 17 while ADAPT‐232 forteÂŽ extract contains 0.07% p ‐tyrosol, 0.33% salidroside and 0.37% rosavin 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The principal raw material used for the production of R. rosea supplements are the rhizomes, and some of the most popular preparations, such as Arctic RootÂŽ (based on the standardised SHR‐5 extract), 11 VitanoÂŽ (WSÂŽ 1375 extract), 12 ADAPT‐232 forteÂŽ (fixed combination of R. rosea , Eleutherococcus senticocus and Schisandra chinensis extracts), 13 are registered as herbal medicines in Europe 14 . The SHR‐5 is defined as R. rosea root and rhizome extract with a herb‐extract ratio 2.5–5:1 (extraction solvent 70% ( v / v ) ethanol), 15 containing 0.15% p ‐tyrosol, 2.14% salidroside and 4.77% rosavins 16 . The WSÂŽ 1375 has an herb‐extract ratio 1.5–5:1 (solvent 67–70% ( v/v ) ethanol) and contains 1% salidroside and 2.71% rosavin, 17 while ADAPT‐232 forteÂŽ extract contains 0.07% p ‐tyrosol, 0.33% salidroside and 0.37% rosavin 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the bioactive effects, salidroside and rosavin have been proposed to be used as markers for quality evaluation of R. rosea [ 28 , 29 ]. The minimal concentration of salidroside and rosavin in high-quality rhizomes of R. rosea is recommended to be 0.8–1% and 3%, respectively [ 30 , 31 , 36 ]. The levels of these two bioactive compounds were either low or absent in many samples of Rhodiola species market products [ 37 , 38 ] reported in the literature ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The various methods used to dry and extract the bioactive compounds of R. rosea have a large impact on the yield of phenyletanes and phenylpropanoids [ 36 , 58 ]. On the other hand, Zomborszki et al (2019) reported that different drying methods did not affect the content of the bioactive compounds of R. rosea [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. baicalensis, H. erinaceus and R. rosea are folk traditional medicinal herbs that gained increasing popularity for their health-promoting properties including antitumor, hepatoprotective, antimicrobial, anti-inflammatory, anti-hyperlipidemic, antidiabetic, cardio-protective, neurotrophic and neuroprotective effects [5,10,15,16,35,[37][38][39][40][41][42][43][44][45][46][47]. In the brain, the beneficial effects of each herb are due to different bioactive compounds, some of which are able to cross the blood-brain-barrier (BBB).…”
Section: S Baicalensis H Erinaceus and R Rosea: Toxicology And Nementioning
confidence: 99%